Language Policy And Practice of the Implementation of English As Medium of Instruction : A Case Study on SMP Tazkia IIBS Malang - Aida Fitrianah Zen (Language-Edu, 2019)
This research reports in-depth investigation based on classroom observation about the practice of English as medium of instruction in teaching academic subject matter and how often the teacher spoke English in class. The data were obtained in ten times observation with the science and math teachers as the participant of the research. Observation sheet checklist was used to measure the frequency of English spoken by the teacher. The finding revealed that the school adopt Cambridge international curriculum. Moreover, the practice of EMI was underachieved. Both of the teachers preferred to use mix language than English fully. Moreover, students’ self-anxiety was occurred as the barrier in successful EMI class. This study suggests that the administrator should emphasize the English language policy communicatively to the teacher therefore they will understand of what teachers ought to do. Further, it is very necessary to implement various teaching strategies to emerge the students’ motivation. Key words: Policy, practice, English as a medium of Instruction